A Systematic Review of Routing Protocols for Vehicular AD Hoc Networks and Recent Developments - Prakruti Kulkarni, (AG Volumes, 2022)
The development of Vehicular Ad Hoc Networks (VANETs), new strong technology that aims to keep passengers secure, has developed. Cars may be linked to the Internet using IEEE 802.11p, which is a technology that can be used with or without existing infrastructure. To solve these issues and get packets to their ultimate destinations on VANETs, there are several current and proposed technologies that may be used. Following the preceding, this study presents a full explanation of several current routing strategies in literature, so that a specific approach may be selected based on its suitability for a given application. Many routing strategies are categorised in the article, with critical examination of each categorization's merits, weaknesses, limits, and uses.